Effects of influenza vaccination in patients with interstitial lung diseases: an epidemiological claims data analysis - Marijic, Pavo; Schwarzkopf, Larissa; Maier, Werner Albert; Trudzinski, Franziska; Schwettmann, Lars; Kreuter, Michael (Annals of the American Thoracic Society, 2022)
Administrative data, Germany, statutory health insurance, survival, vaccination rate